2016
DOI: 10.1007/s00268-016-3759-8
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of the World Health Organization Trauma Care Checklist Program in 11 Centers Across Multiple Economic Strata: Effect on Care Process Measures

Abstract: Implementation of the WHO Trauma Care Checklist was associated with substantial improvements in patient care process measures among a cohort of patients in diverse settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
66
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(74 citation statements)
references
References 37 publications
3
66
0
3
Order By: Relevance
“…Trauma is an inevitable cause of death across the world [2]. Trauma injuries cause higher mortality rates compared to AIDS (Acquired immune deficiency syndrome) , Malaria and tuberculosis [3]. The number of deaths caused by trauma is estimated to be 5.8 million per year [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Trauma is an inevitable cause of death across the world [2]. Trauma injuries cause higher mortality rates compared to AIDS (Acquired immune deficiency syndrome) , Malaria and tuberculosis [3]. The number of deaths caused by trauma is estimated to be 5.8 million per year [4].…”
Section: Introductionmentioning
confidence: 99%
“…According to estimations, the implementation of plans for improving care services to trauma patients will save 1.730 to 1.964 people annually [3]. In Iran, trauma is considered to be an important issue.…”
Section: Introductionmentioning
confidence: 99%
“…Trauma centers are also increasingly adopting resuscitation checklists, showing positive impacts on team performance [17]. These initial experiences have confirmed that checklists may play a critical role in emergency situations when the pressure to perform is high [3].…”
Section: Introductionmentioning
confidence: 99%
“…Так, од-ночасне виявлення уражень черепа і головного мозку у постраждалого з закритою травмою жи-вота виявляється в 19,3 -38,8 % [3]; з закритою травмою грудної клітини -в 32,1 -65,4 % [4]. Та-кі характеристики абдомінальної та торакальної травми, поєднаної з черепно-мозковою травмою (ЧМТ), як тяжкий клінічний перебіг, труднощі ді-агностики і лікування, високий відсоток усклад-нень тільки підкреслюють актуальність даної про-блеми [6]. Всі ці складові в подальшому знаходять відображення у високих показниках летальності -від 33,6 до 94,2 % при тяжкій ЧМТ, а також висо-кому відсотку інвалідизації -до 29,1 %.…”
unclassified
“…Незважаючи на широке і ефективне викорис-тання в даний час ендовідеохірургічних техноло-гій, чітке визначення місця лапароскопії (тора-коскопії) в алгоритмі діагностики і лікування по-єднаних пошкоджень живота чи грудної клітки з черепно-мозковою травмою є до кінця невиріше-ною проблемою [6].…”
unclassified